Efficacy and safety of the blood-based cardioplegia solution Huaxi-1 in cardiopulmonary bypass surgery: protocol for a multicentre randomised controlled trial - Tao Chen; Li Zhang; Jing Yang; Xue Gao; Liwei Wang; Wei Yan; Yinghui Shi; Chunle Wang; Zhiqiang Wen; Tingfang Zou; Yingyuan Wu; Fumin Yu; et al. (BMJ Open)
Introduction Cardioplegia during cardiopulmonary bypass is essential for ensuring a surgical field free of blood and cardiac movement. Numerous cardioplegia solutions are available, but consensus guidelines about the safest or most effective do not exist. The present trial will compare the Huaxi-1 cardioplegia solution, which has been used since 2006 with good results at a major Chinese cardiac centre not involved in this trial, with the widely used Custodiol histidine-tryptophan-ketoglutarate (HTK) solution in terms of safety and efficacy at inducing cardiac arrest and protecting the myocardium during bypass.Methods and analysis A total of 160 adult patients undergoing elective cardiac surgery requiring cardiopulmonary bypass and cardioplegic arrest will be recruited at four medical centres in China. Recruitment is planned to begin on 1 November 2024, and is expected to conclude by 31 October 2025. Eligible patients will be randomly allocated 1:1 to receive either Huaxi-1 or HTK cardioplegia solution. The primary endpoint is the peak level of high-sensitivity cardiac troponin T (hs-cTnT) within 48 hours after surgery between the two groups. The secondary endpoints include levels of myocardial injury markers such as the creatine kinase-myocardial band (CK-MB) and cardiac troponin I at baseline and at 6, 12, 24 and 48 hours after surgery. The two groups will also be compared in terms of how left ventricular ejection fraction changes from baseline and in terms of the rate of spontaneous cardiac recovery. Data will be analysed using SAS V.9.4.Ethics and dissemination This trial has been approved by the ethics committees at Guangdong Provincial People’s Hospital (lead site) and the three other study sites. The results of the study will be published in peer-reviewed journals and presented at international conferences.Trial registration number ChiCTR2400089689 (www.chictr.org.cn).